Implementasi Peraturan Daerah Nomor 5 Tahun 2020 Terhadap Pembangunan Aksesibilitas Pariwisata di Kawasan Wisata Bukit Lawang Kabupaten Langkat - Wahyudi, Eka; Hajar, Siti (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
This study, entitled "Implementation of Regional Regulation Number 5 of 2020 on the Development of Tourism Accessibility in the Bukit Lawang Tourism Area, Langkat Regency," aims to analyse how the implementation of the regional regulation affects the development of tourism accessibility in Bukit Lawang. The background of this study is based on the importance of the tourism sector in the regional economy, as well as the need to improve accessibility for all tourists, including people with disabilities, in order to create an inclusive and sustainable tourism experience. The method used in this study is a qualitative approach with data collection techniques through in-depth interviews with relevant informants, such as government officials, village heads, business actors, and tourists. The data obtained are analysed to understand communication, resources, dispositions, and bureaucratic structures that influence the implementation of regional regulations. The results of the study indicate that the implementation of Regional Regulation Number 5 of 2020 has been carried out with quite effective communication efforts between the regional government and the community